Asas Itikad Baik Dalam Penggantian Ongkos Pasca Perbuatan Sukarela - Saputra, Febrianto; Gultom, Elisatris (Universitas Muhammadiyah Yogyakarta, 2024)
The gestor, in the course of voluntary management, often incurs various expenses. Reimbursement of these management costs can be claimed from the dominus (Article 1357 of the Civil Code). However, the gestor's position may become vulnerable if the dominus did not request such management, especially with the application of Article 1358 of the Civil Code, and if the dominus fails to recognize the existence of a legal relationship. This study aims to understand how the principle of good faith is applied in the reimbursement of costs arising from voluntary actions and its function as a guideline to balance rights and obligations, potentially preventing disputes arising from differing views on zaakwaarneming cost reimbursements. This research adopts normative legal research methods. The findings reveal that, although Articles 1354–1358 of the Civil Code provide a legal foundation for zaakwaarneming, the gestor's position often remains vulnerable, particularly regarding cost reimbursements following voluntary actions. In this context, the principle of good faith functions as both a moral standard and a legal mechanism to ensure that the relationship between the gestor and dominus is proportional, rational, and does not harm either party. Through the principle of good faith, cost reimbursements can be conducted fairly and appropriately without resorting to litigation, given the cooperative nature underlying the zaakwaarneming relationship. This relationship is not merely moral-social but also constitutes a tangible legal relationship. The principle of good faith ensures that the dominus fulfills their obligations fairly and transparently, requiring both parties to act with propriety and appropriateness. This fosters not only a healthy and cooperative legal relationship but also reinforces moral-social values in their interactions